ANALYSIS OF THE STATE OF PROBLEM-BASED ASSETS IN COMMERCIAL BANKS AND THE PRACTICE OF THEIR REDUCTION (Academicia Globe: Inderscience Research, 2024)
The article presents factors for the emergence of problem assets in commercial banks, their analysis, and proposals for reducing problem assets. Based on the study and observation of concepts such as "problem asset," "problem loan," "classification of problem assets," and "passive loan" in the scientific article, relevant approaches and recommendations have been formulated, highlighting the main mechanisms used to repay existing problem loans in the bank's portfolio.